The Influence Of Audit Committee Effectiveness, Audit Opinion, And Firm Size On Financial Reporting Fraud - Febrian, Yudha Eka (Journal of Economics and Business (JECOMBI), 2025)
The aim of this research is to determine the effect of audit committee independence, audit committee financial expertise, audit committee work meetings, audit opinion and company size on fraudulent financial reporting. The research method uses quantitative methods. The research design consists of a descriptive design and a causal design. The sampling technique uses purposive sampling with a total sample of 25 financial sector companies in the insurance and multi-finance (financing) sub-sectors listed on the IDX in 2019-2023, where the research sample data is 125 sample data. Data analysis uses multiple linear regression analysis with the SPSS Version 23 program. Based on the results of data analysis, it is known that the Adjusted R Square value is 0.264. This shows that 26.4% of the variation in fraudulent financial reporting variables can be explained by the variables audit committee independence, audit committee financial expertise, audit committee work meetings, audit opinion and company size, while the remaining 73.6% is explained by other variables. which was not researched. From the results of hypothesis testing, it is known that audit committee independence has a negative effect on fraudulent financial reporting, audit committee financial expertise has no effect on fraudulent financial reporting, frequency of audit committee meetings has a positive effect on fraudulent financial reporting, audit committees have a negative effect on fraudulent financial reporting, and company size ( size) has a negative effect on fraudulent financial reporting.